HUBUNGAN CITRA TUBUH DAN DUKUNGAN TEMAN SEBAYA DENGAN KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA REMAJA PUTRI DI MADRASAH ALIYAH NEGERI 7 JAKARTA TAHUN 2020 - Eka Nurwidyanti (2021)
Chronic energy deficiency (KEK) is a nutritional problem that still often occurs in adolescents, especially girls. The occurrence of chronic energy deficiency (KEK) in adolescents is influenced by many things, one of which is an assessment of the physical shape of the body or what is called body image and peer support. The risks that can be caused by KEK are various diseases, ranging from infectious diseases to hormonal disorders that can have a negative impact on the health of adolescents. The purpose of this study was to determine the relationship between body image and peer support with chronic energy deficiency at Madrasah Aliyah Negeri 7 Jakarta in 2020. This study used a quantitative analytical research method with a cross-sectional approach, with a total sample of 135 students using this technique. convenience sample sampling. The results of this study showed a relationship between body image (p = 0.017) and peer support (p = 0.000) with chronic energy deficiency (KEK). The conclusion of this study is that there is a relationship between body image and peer support with chronic energy deficiency (KEK). Therefore adolescents are advised to seek more information related to nutrition and ways to prevent KEK.